2011
DOI: 10.1021/am2001899
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Buried Interfacial Structures of Epoxy Resins Used as Underfills Studied by Sum Frequency Generation Vibrational Spectroscopy

Abstract: Flip chip technology has greatly improved the performance of semiconductor devices, but relies heavily on the performance of epoxy underfill adhesives. Because epoxy underfills are cured in situ in flip chip semiconductor devices, understanding their surface and interfacial structures is critical for understanding their adhesion to various substrates. Here, sum frequency generation (SFG) vibrational spectroscopy was used to study surface and buried interfacial structures of two model epoxy resins used as under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…5,6 Several techniques have been utilized for probing buried interfaces, such as near-edge X-ray absorption ne structure spectroscopy (NEXAFS) combined with delamination techniques 7,8 and vibrational sum frequency generation (SFG) spectroscopy. 9,10 Nonetheless, a more readily accessible method is needed for direct structural characterization of such interfacial layers in semiconductor thin lms.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Several techniques have been utilized for probing buried interfaces, such as near-edge X-ray absorption ne structure spectroscopy (NEXAFS) combined with delamination techniques 7,8 and vibrational sum frequency generation (SFG) spectroscopy. 9,10 Nonetheless, a more readily accessible method is needed for direct structural characterization of such interfacial layers in semiconductor thin lms.…”
Section: Introductionmentioning
confidence: 99%
“…reported a study using SFG-VS to derive molecular orientations of epoxy molecules cured on surfaces of various substrates. 113 However, SFG-VS signal from the buried epoxy/polymer interface was so weak that the vibrational peaks can barely be resolved. 113 Zhang et al.…”
Section: Understanding Adhesion Mechanism At Polymer Interfacesmentioning
confidence: 99%
“…In 2011, Vázquez et al reported a study using SFG-VS to derive molecular orientations of epoxy molecules cured on surfaces of various substrates. 113 However, SFG-VS signal from the buried epoxy/polymer interface was so weak that the vibrational peaks can barely be resolved. 113 Zhang et al improved the SFG-VS technique for the study of buried epoxy interfaces by using a near TIR geometry which allowed to detect weak signal contributed by the interface molecules.…”
Section: Epoxy Adhesivesmentioning
confidence: 99%
See 2 more Smart Citations